Slice2Volume: fusion of multimodal medical imaging and light microscopy data of irradiation-injured brain tissue in 3D - Soltwedel, Johannes; Suckert, Theresa; Beyreuther, Elke; Schneider, Moritz; Boucsein, Marc; Bodenstein, Elisabeth; Nexhipi, Sindi; Stolz-Kieslich, Liane; Krause, Mechthild; von Neubeck, Cläre; Haase, Robert; Lühr, Armin; et al. (Radiotherapy and oncology, 2023)
Comprehending cellular changes of radiation-induced brain injury is crucial to prevent and treat the pathology. We provide a unique open dataset of proton-irradiated mouse brains consisting of medical imaging, radiation dose simulations, and large-scale microscopy images, all registered into a common coordinate system. This allows dose-dependent analyses on single-cell level.
Online verfügbar 28. Februar 2023, Artikelversion 20. März 2023
Gesehen am 15.06.2023